INSILICO DESIGNING AND SYNTHESIS OF IMIDAZOLE DERIVATIVES AS ANTIMICROBIAL AGENT - RAJKUMAR MOHANTA,; SUSANTA KUMAR SAHU, (International Journal of Pharma and Bio Sciences, 2013)
To emphasis the designing of drug molecule for increased the potency to recovery the infectious diseases by developing interaction of ligands with target proteins in insilico method , provided for selecting a new series of title compounds for synthesis. Title compounds 3-chloro-1-[1-(2-hydroxyethyl)-2-methyl-1H-imidazol-5-yl]-4-substituted phenylazetidin-2-one (3a1-5) were synthesized by reaction of 2-(2-methyl-5-{[(substituted)phenylmethylidene]amino}-1H-imidazol-1-yl)ethanol (2a1-5) and triethanolamine in the presence of chloro acetyl chloride with constant stirring for 7hrs. The compounds were established on the basis of their elemental analysis, FT-IR, 1HNMR and MS spectral data. The lipophilicity (logP) and ADME toxicity study was proven the drug likeness properties as in compounds 3a1-5 and activity efficacy of the 3a1-5 were typical which predicted by the best free energy poses interaction of target protein as compared to standard drugs. Thus it was observed that, both insilico and in vitro studies were parallely indicated the activities and identified the imidazole derivatives acted as an antimicrobial agent.